Financial development and economic growth: A new empirical analysis - Michael Graff (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 1999)
The paper describes tests of hypotheses from economic history concerning the significance of financial development as a determinant of economic growth. It goes beyond the existing studies in drawing on a large panel data set covering 93 countries from 1970-90 and includes a new proxy for the resource input into the financial system. Moreover, interaction effects between financial development and catching-up as well as education are considered. Finally, to clarify causal relationships, a two-wave path model is estimated. It is shown that during the 1970s and 1980s finance was a significant and predominantly supply-leading determinant of growth.
Keywords: 330; Finanzsektor; Entwicklung; Wirtschaftswachstum; Neue Wachstumstheorie; Schätzung; Welt